Uji Potensi Antifungi Koloid Perak Nanopartikel (AgNPs) terhadap Aspergillus niger - Witiyasti Imaningsih; Ahmad Budi Junaidi; Imam Kurniawan (Universitas Lambung Mangkurat, 2020)
Silver nanoparticles (AgNPs) antimicrobial activity has known to be more effective than any antibiotics. Diseases which caused by pathogenic fungi has increased because of the ability of pathogenic fungi to survive against antibiotic. Silver nanoparticles have the ability to inhibit the transport material from the environment around microorganisms. The aims of this study are to measure the value of Minimal Inhibitory Concentrations (MIC) and Minimal Fungicidal Concentrations (MFC) of colloidal AgNPs to Aspergillus niger. MIC and MBC are determined based on the correlation between concentration of colloidal AgNPs and biomass of Aspergillus niger. Measurement of Aspergillus niger biomass based on treatments of Aspergillus niger spore which was applied by various concentrations of the colloidal AgNPs. Aspergillus niger spores were incubated for 5 days at room temperature above orbital shacker. MIC of colloidal AgNPs was Aspergillus niger was 1,18 µg·L-1 . MFC of colloidal AgNPs to Aspergillus niger is 60,57 µg·L-1.